Вклад у розвиток української культури видатним соціально-політичним і науковим діячем Михайлом Грушевським - Кириченко, А. А. (ХНУРЕ, 2019)
I believe that our Ukrainian nation still has so much spontaneous power, so much vitality that you will not be beaten by any theorems that it will break through its own elemental force through all artificial obstacles - until we kill ourselves these forces of ours apathy, inactivity.